2022
DOI: 10.20944/preprints202202.0265.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female Mice Susceptibility to the Dietary Omega-3/Omega-6 Fatty Acid Ratio: Effects on Adult Hippocampal Neurogenesis and Glia

Abstract: Maternal intake of the polyunsaturated fatty acids omega-3 (n-3 PUFA) and omega-6 (n-6 PUFA) impacts hippocampal neurogenesis during development, an effect that may extend to adulthood by altering adult hippocampal neurogenesis (AHN). n-3 PUFA and n-6 PUFA are precursors of inflammatory regulators that potentially affect AHN and glia. Additionally, n-3 PUFA dietary supplementation may present a sexually dimorphic action in the brain. Therefore, we postulated that dietary n-6/n-3 PUFA balance shapes the adult D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that the vast majority of studies in neurosciences, and specifically regarding lipid-diet effects on memory and cognition, have been exclusively conducted in male animals, even though the assumption that females are intrinsically more variable due to the estrous cycle has been disproved and that actually the estrous cycle does not usually need to be considered [49]; therefore, we focused our investigation on female brains as they are more poorly investigated. Indeed, recent reports indicate that the neuroprotective effects of n-3 LCPUFAs differ between male and female animals, related in part to the interactions of estrogens with DHA in the brain [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the vast majority of studies in neurosciences, and specifically regarding lipid-diet effects on memory and cognition, have been exclusively conducted in male animals, even though the assumption that females are intrinsically more variable due to the estrous cycle has been disproved and that actually the estrous cycle does not usually need to be considered [49]; therefore, we focused our investigation on female brains as they are more poorly investigated. Indeed, recent reports indicate that the neuroprotective effects of n-3 LCPUFAs differ between male and female animals, related in part to the interactions of estrogens with DHA in the brain [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Another noteworthy point is that ω-6 PUFAs and ω-3 PUFAs, as the precursors of DHA, EPA, AA, and LA, are clearly involved in the pathogenesis of depression [ 65 ]. Studies have shown that ω-3 PUFAs exert anti-inflammatory effects in the brain by regulating microglia function to maintain homeostasis, which improve fatty acids for the pathogen.…”
Section: Depression-associated Seh Promotes Liver Dysfunction and Bre...mentioning
confidence: 99%
“…Studies have shown that ω-3 PUFAs exert anti-inflammatory effects in the brain by regulating microglia function to maintain homeostasis, which improve fatty acids for the pathogen. At the same time, ω-6 PUFAs have been considered as promoting factors of inflammation, while the ability of dietary LA to increase the levels of inflammatory markers is influenced to some degree by the level of adiposity [ 65 , 125 ]. The ratio of ω-6 PUFAs/ω-3 PUFAs is considered to affect the balance of lipid metabolism [ 125 , 126 ].…”
Section: Depression-associated Seh Promotes Liver Dysfunction and Bre...mentioning
confidence: 99%